POLA TRANSAKSI PADA COMMODITY EXCHANGE : Perspektif Hukum Islam - Efrinaldi Efrinaldi (AL-ISTINBATH : Jurnal Hukum Islam, 2017)
Transactions on commodity exchange as futures trading are seen from the contract cycles as a pure trade activity, reduce the risk of profit from buying and selling, as a result of price fluctuations on trading commodities. Price fluctuations can be predicted and transactions begin with analysis, while risk can be protected. The type of transaction on physical goods and the spot market, in the perspective of Islamic economic law, can be tolerated. Certain types of trade (al-tijarah) have been arranged in syara ', because indeed the forms of transactions in such trades have been tolerated in the time of the Prophet. Spot markets, such as transactions of agricultural products, livestock, minerals, handicrafts, industry, and so forth. While transactions service that are non-physical, eg rent (al-ujrah) and wage-hire (al-ijarah). The aim of trade is essentially objects of economic value with the availability of goods in aqad assemblies (at the time of the transaction). In the Islamic review, this also applies to items that are not available or without presenting the goods at the time of the transaction, provides the ordered item is concrete of its nature. This is non-existent form of trade (such as al-salam), in Islamic law studies, depends on seller's effective control and ability to deliver. There is a protection against the value of goods transacted from probabilities that are inconsistent with the properties specified in the aqad assemblies, protection against the interests of consumer from loss (cut loss) and no disappointment in the future. In futures trading, it is known as the term of hedging